4 intregi si 1/2 = ( 4 x 2 + 1)/2 = 9/2
(6/112 + 3/56 : 1/14) : 9/2 = ( 6/112 + 3/56 × 14/1) : 9/2=
→ simplific pe 14 cu 56 prin 14 = 1/4
= ( 6/112 + 3/4) × 2/9 = → amplific fractia 3/4 cu 28
= [ 6/112 + (28 x 3 ) / ( 28 x 4) ] × 2/9 =
= ( 6/112 + 84/112) × 2/9 =
= 90 /112 × 2/9 = → simplific pe 90 cu 9 = 10 /1, dar si pe 2 cu 112
= 10/56 =
= 5/28
h)
4 intregi 2/3 = ( 4 x 3 + 2)/3= 14/3
1 intreg si 3/7 = (1 x 7 + 3) / 7 = 10/7
[14/3 × ( 15/54 - 4/18 ) ] : [ ( 10/7 + 1/14 ) : 3/7]=
= [ 14/3 × ( 5/18 - 4/18 )] : [ ( 20/14 + 1/14) × 7/3]=
= ( 14/3 × 1/18) : ( 21/14 × 7/3)= → simplific pe 21 cu 3 = 7, dar si pe 7 cu 14
= 7/27 × 7/2 =
= 49/54